Penerapan Prinsip Hukum Islam dalam Pengelolaan Sampah di Makassar - Muhaemina Muhaemina; Nur Aisyah; Kurniati Kurniati (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
Solid waste management in Makassar City constitutes a strategic issue that extends beyond technical and administrative concerns to encompass legal, ethical, and socioreligious dimensions. Although the local government has established regulatory frameworks and policy instruments for waste management, empirical conditions reveal a persistent gap between legal norms and their implementation, as reflected in high waste generation rates, weak source segregation, limited public participation, and increasing pressure on landfill capacity. This study aims to analyze the effectiveness of waste management in Makassar City from the perspective of Islamic law and to examine the potential integration of Sharia principles in strengthening sustainable environmental governance. The research employs a qualitative approach with a descriptive-analytical design based on policy analysis, literature review, and theoretical synthesis of Islamic legal doctrines, particularly maqāṣid al-sharīʿah and fiqh al-bī’ah. The findings indicate that, despite the existence of adequate local legal instruments, waste management practices remain ineffective due to insufficient internalization of ethical values, weak law enforcement, and limited behavioral change within society. From the perspective of Islamic law, these conditions demonstrate the incomplete realization of the principles of amanah (trust and responsibility), maslahah (public interest), and the prevention of harm (lā ḍarar wa lā ḍirār) in both governmental practice and public conduct, thereby undermining the objectives of protecting human life and the environment. The implications of this research highlight the importance of synergizing positive law and Islamic legal principles to promote environmentally sustainable governance oriented toward long-term public welfare.